Bioinformatics analysis and molecular modelling of Glucose 6-phosphate dehydrogenase (G6PDH) from Gluconobacter oxydans - Hazirah Mohd. Asandi, 1994- , author 612674 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Project Paper (Sarjana Muda Sains (Biologi)) - Universiti Teknologi Malaysia, 2017